2022
DOI: 10.13057/biodiv/d230238
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and status of day butterflies (Lepidoptera: Rhopalocera) in different plant associations of the Edough Forest Massif (Northeastern Algeria)

Abstract: Abstract. Laref N, Rezzag-Beddida R, Boukheroufa M, Sakraoui R, Henada RLI, Hadiby R, Sakraoui F. 2021. Diversity and status of day butterflies (Lepidoptera: Rhopalocera) in different plant associations of the Edough Forest Massif (Northeastern Algeria). Biodiversitas 23: 954-961. The current study seeks to evaluate the biodiversity and the structure of the Lepidoptera, Rhopalocera stand in the Edough mountain range, Northeastern Algeria. The main objective is to analyse specific and dynamic fluctuations depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Besides Tennent, who produced a systematic and ecological list of butterflies (1996), Samraoui (1998) inventoried butterflies occupying the most interesting habitats in North-eastern Algeria. Other investigations were made like those of Chakali et al (2002); Frahtia (2005); Remini and Moulaï (2015); Saad and Bounaceur (2018); Kacha et al (2017Kacha et al ( , 2020; Allache and Demnati (2020); Berkane et al (2019Berkane et al ( , 2021 and recently Laref et al (2022) in the Edough Forest Massif.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides Tennent, who produced a systematic and ecological list of butterflies (1996), Samraoui (1998) inventoried butterflies occupying the most interesting habitats in North-eastern Algeria. Other investigations were made like those of Chakali et al (2002); Frahtia (2005); Remini and Moulaï (2015); Saad and Bounaceur (2018); Kacha et al (2017Kacha et al ( , 2020; Allache and Demnati (2020); Berkane et al (2019Berkane et al ( , 2021 and recently Laref et al (2022) in the Edough Forest Massif.…”
Section: Introductionmentioning
confidence: 94%
“…While most butterflies are found in herbaceous habitats like grasslands and lawns (Börschig et al 2013), they can also be found in forest environments due to the composition, structure, and variability of plant communities. Edges and herbaceous intra-forest settings (Clearings, forest roads and open stands) can thus act as refuges, providing not only favorable microclimatic conditions but also nectar resources and host plants (Laref et al 2022). Forest environments, according to Dajoz (2007), are excellent biodiversity reservoirs, more biologically diverse than any other terrestrial ecosystem, and they provide numerous benefits for wildlife, both in terms of botanical diversity and the spatial-temporal distribution of different plant species, providing ecological resources that meet the vital needs of animals (Budiaman et al 2016).…”
Section: Introductionmentioning
confidence: 99%